Acid-Activated Natural Clay for Fe(III) Adsorption: An Integrated Study of Mechanisms, Kinetics, and Thermodynamics - Afandy, Moh. Azhar; Herliawan, Deden Jajang Harly; Nirwansyah; Sawali, Fikrah Dian Indrawati (Indonesian Journal of Environmental Management and Sustainability, 2025)
The increasing contamination of water by Fe(III) ions from industrial activities, particularly in nickel-producing regions such as Morowali, presents serious environmental and public health concerns. Among various treatment approaches, adsorption stands out as an efficient and cost-effective method, especially using natural clay modified by acid treatment. This study aims to investigate the characterization, adsorption kinetics, and thermodynamic behavior of Fe(III) removal using acid-modified natural clay (NC) derived from Morowali. The clay was activated using sulfuric acid (H2SO4), followed by physicochemical characterization and batch adsorption experiments to assess its removal performance. Adsorption kinetics were analyzed using Pseudo-First Order (PFO), Pseudo-Second Order (PSO), Intraparticle Diffusion (IPD), and Liquid Film Diffusion (LFD) models to elucidate the adsorption mechanism. Furthermore, thermodynamic parameters such as Gibbs free energy (deltaG), enthalpy (deltaH), and entropy (deltaS) were calculated to determine the nature of the adsorption process. The results showed that NC exhibited a considerable adsorption capacity for Fe(III), with PSO providing the best kinetic fit, indicating chemisorption control. Thermodynamic analysis confirmed the spontaneous and endothermic nature of the process. These findings demonstrate the potential of acid-modified clay from Morowali as a low-cost and locally available adsorbent, contributing to sustainable water treatment strategies in industrial regions.